A modified clinicopathological tumor staging system for survival prediction of patients with penile cancer. Issue 1 (23rd November 2018) - Li, Zai‐Shang; Ornellas, Antonio Augusto; Schwentner, Christian; Li, Xiang; Chaux, Alcides; Netto, Georges; Burnett, Arthur L.; Tang, Yong; Geng, JiunHung; Yao, Kai; Chen, Xiao‐Feng; Wang, Bin; et al.
Abstract: Background: The 8th American Joint Committee on Cancer tumor–node–metastasis (AJCC‐TNM) staging system is based on a few retrospective single‐center studies. We aimed to test the prognostic validity of the staging system and to determine whether a modified clinicopathological tumor staging system that includes lymphovascular embolization could increase the accuracy of prognostic prediction for patients with stage T2–3 penile cancer. Methods: A training cohort of 411 patients who were treated at 2 centers in China and Brazil between 2000 and 2015 were staged according to the 8th AJCC‐TNM staging system. The internal validation was analyzed by bootstrap‐corrected C‐indexes (resampled 1000 times). Data from 436 patients who were treated at 15 centers over four continents were used for external validation. Results: A survivorship overlap was observed between T2 and T3 patients ( P = 0.587) classified according to the 8th AJCC‐TNM staging system. Lymphovascular embolization was a significant prognostic factor for metastasis and survival (all P < 0.001). Based on the multivariate analysis, only lymphovascular embolization showed a significant influence on cancer‐specific survival (CSS) (hazard ratio = 1.587, 95% confidence interval = 1.253–2.011; P = 0.001). T2 and T3 patients with lymphovascular embolization showed significantly shorter CSS than did those without lymphovascular embolization ( P < 0.001). Therefore, a modified clinicopathological staging system was proposed, with the T2 and T3 categories of the 8th AJCC‐TNM staging system being subdivided into two new categories as follows: t2 tumors invade the corpus spongiosum and/or corpora cavernosa and/or urethra without lymphovascular invasion, and t3 tumors invade the corpus spongiosum and/or corpora cavernosa and/or urethra with lymphovascular invasion. The modified staging system involving lymphovascular embolization showed improved prognostic stratification with significant differences in CSS among all categories (all P < 0.005) and exhibited higher accuracy in predicting patient prognoses than did the 8th AJCC‐TNM staging system (C‐index, 0.739 vs. 0.696). These results were confirmed in the external validation cohort. Conclusions: T2–3 penile cancers are heterogeneous, and a modified clinicopathological staging system that incorporates lymphovascular embolization may better predict the prognosis of patients with penile cancer than does the 8th AJCC‐TNM staging system. Trial registration This study was retrospectively registered on Chinese Clinical Trail Registry: ChiCTR16008041 (2016‐03‐02). http://www.chictr.org.cn